PENERAPAN MEDIA TUTUP BOTOL BEKAS UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWADI RA MUSLIMAT NU 007 GANDU I MLARAK PONOROGO - Abdah Munfaridatus Sholihah; Siti Fatimah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2020)
Pre-school age is an effective age for developing various potentials of children, one of which is the potential for cognitive development in children. Mathematics becomes increasingly important in the age of technology, the more important it is that children learn mathematics at home and at school. Basically the ability of children is very extraordinary in capturing information at the same time with various senses, for example they are playing, they also keep learning. Then in the field it has been found that there are problems in learning activities, especially in the ability to count. In general they have been able to count in sequence while lifting their fingers, but in the concept of addition and subtraction using the help of their fingers, some are still confused. This study reports the results of the study, with the formulation of the problem; (1) How can the application of used bottle cap media to improve students 'numeracy skills in RA Muslimat NU 007 Gandu Mlarak Ponorogo ?, (2) Can the application of used bottle cap media improve students' numeracy ability in RA Muslimat NU 007 Gandu Mlarak Ponorogo? This research was conducted at RA Muslimat NU 007 Gandu Mlarak Ponorogo. In this study, the Classroom Action Research method was carried out in 3 cycles through the stages in which learning used used used bottle caps. Data collection techniques through observation, oral tests, and documentation. Based on the results of data analysis, it can be concluded that: (1) The application of used bottle cap media to improve students' numeracy ability has been planned through RPPH and actions have been carried out in Cycle I to Cycle III, (2) The application of the used bottle cap media can improve the ability to count student at RA Muslimat NU 007 Gandu Mlarak Ponorogo.